NURSES’ KNOWLEDGE, ATTITUDES, AND PRACTICES OF UNIVERSAL PRECAUTION TOWARD HIV/AIDS TRANSMISSION - Wiwi Mardiah; Ayu Prawesti Priambodo (Universitas Airlangga, 2014)
Introduction: The incidence of HIV/AIDS is continuing increase in Indonesia. Nurses are the most risky occupations of gaining transmitted infection. This study aimed to identify the nurses’ knowledge, attitudes, and practices of universal precaution toward HIV/AIDS transmission in a hospital.Methods: Descriptive correlation study was a design of this study. Ninety nurses were recruited using proposionate stratifi ed random sampling. The instrument was KAP (Knowledge Attitudes Practices) questionnaire consisted of demographic data form, knowledge, attitude, and self-reported practices regarding universal precaution. The collected data, then were analyzed both descriptively and inferentially by using pearson product moment correlationResults: The majority of respondents reported experience of sharp injuries. More than a half of respondents had a good knowledge level about universal precaution and HIV/AIDS transmission, and showed favorable attitude toward caring for HIV/AIDS patients. There was signifi cant correlation between knowledge and practice (r=0,271 p=< 0, 01), whereas no correlation between knowledge and attitude score, and attitude and practice score.Conclusion: It is need to be taken immediately to prevent and minimize the occurrence of sharp injuries among nurses in order to assure safety working condition to improve the productivity of nursing service. Updating knowledge, developing positive attitude, and continuing evaluation should be done simultaneously to improve the nurses’ competence in preventing the occupational related-disease.